TEXTUAL INTERPRETATION OF THE COWS OF BASHAN AND CRITICS OF AMOS IN AMOS 4: 1-3 - Bastian, Yonas; Dirgaprimawan, Bernadus (Journal of Asian Orientation in Theology, 2024)
The book of Amos, chapter 4:1-3, illustrates Amos's strategic choice in rebuking the government officials who indulge in luxury. Amos compares these elites to the cows of Bashan. Through rhetorical critique of that passage, this article aims to analyze the motives why Amos deliberately uses the metaphor the cows of Bashan. Amos wants his criticism that he conveys to be right on target to his interlocutors. He recognized that his interlocutors were not ordinary people; they were part of the elite class accustomed to luxurious lifestyles. Taking advantage of their husbands' high positions, they enriched themselves while turning a deaf ear to the grievances of the common people. Therefore, this article believes that through the metaphor of the cows of Bashan and the hook punishment, Amos makes a sarcastic satire because it is seen as effective in touching upon the sensitivities of these government officials. Amos chose the metaphor of the cows of Bashan also because of the socio-geographical context that is very close to their lives. Through this sarcastic satire, Amos successfully conveyed his theological message cleverly: that God does not remain silent in reproaching anyone who disregards the marginalized and oppressed.